Barriers to equitable healthcare services for under-five children in Ethiopia: a qualitative exploratory study - Hailu Fekadu; Wubegzier Mekonnen; Aynalem Adugna; Helmut Kloos; Damen Hailemariam (BMC, 2024)
Abstract Background Disparities in child healthcare service utilization are unacceptably high in Ethiopia. Nevertheless, little is known about underlying barriers to accessing child health services, especially among low socioeconomic subgroups and in remote areas. This study aims to identify barriers to equity in the use of child healthcare services in Ethiopia. Methods Data were obtained from 20 key- informant interviews (KII) and 6 focus group discussions (FGD) with mothers and care givers. This study was conducted in Oromia Region, Arsi Zone, Zuway Dugda District from June 1-30, 2023. The study participants for this research were selected purposively. The information was collected based on the principle of saturation after sixteen consecutives interview were conducted. Both KII and FGD were audio-recorded and complementary notes were taken to record observations about the participants' comments and their interactions. Each interview and FGD data were transcribed word-for-word in the local Afaan Oromo and Amaharic languages and then translated to English language. Finally, the data were analyzed thematically using NVivo 14 software and narrated in the linked pattern of child health service utilization. Results This study identified six major themes which emerged as barriers to healthcare utilization equity for caregivers and their -under-five children. Barriers related to equity in low level of awareness regarding need, low socioeconomic status, geographical inaccessibility, barriers related to deficient healthcare system, community perception and cultural restrictions, and barriers of equity related to political instability and conflict. The most commonly recognized barriers of equity at the community level were political instability, conflict, and a tremendous distance to a health facility. Transportation challenges, poor functional services, closure of the health facility in working hours, and lack of proper planning to address the marginalized populations were identified barriers of equity at organizational or policy level. Conclusion This study showed that inequity in child healthcare utilization is an important challenge confronting Ethiopia. To achieve equity, policy makers and planners need to change health policy and structure to be pro-poor. It is also necessary to improve the healthcare system to increase service utilization and access for impoverished women, individuals with lower levels of education, and residents of isolated rural areas. Furthermore, context specific information pertaining to cultural barriers and political ecology are required.